PENINGKATAN KETERAMPILAN BERMAIN PIANIKA MELALUI METODE DEMONSTRASI PADA SISWA KELAS VI SD KARTIKA XVII "“ 1 PONTIANAK - Likudanoe, Winaldi Ridwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This look at targets to decorate students' skills in playing the melodica thru the demonstration approach. The studies takes the form of school room action studies, with 30 6th-grade college students as the subjects. The look at is performed in two cycles, each which includes 4 degrees: planning, implementation, statement, and reflection. The research tool is a abilities check sheet. The effects display that inside the first cycle, regarding the hand position thing, college students nevertheless make errors where the melodica is positioned on the table and now not held using the left hand. In terms of respiratory approach, some students still use mouth respiratory, ensuing in fantastically short sounds. regarding fingering, college students' fingers are nonetheless stiff in pressing the melodica keys. In phrases of fluency, many college students aren't but fluent in gambling the C important scale due to stiff fingering, making the transition among keys no longer clean. within the second cycle, in phrases of hand function, college students can now hold the melodica successfully, with the left hand maintaining the tool and the frame upright. concerning respiration method, some students can now blow the melodica gradually, generating longer sounds. In fingering, college students can press the melodica keys properly and without stiffness. In terms of fluency, all college students can now play songs with accurate strategies. it is able to be concluded that the demonstration method can enhance students' abilities in playing musical instruments.